The analysis of continence after posterosagital anorectoplasty in anorectal malformation patients in Wahidin Sudirohusodo hospital of Makassar - Lawile, Alwi; Mantu, Farid Nur; Mariana, Nita; Seweng, Arifin (International Journal of Research in Medical Sciences, 2019)
Background: The management of anorectal malformations universally uses posterior sagittal anorectoplasty (PSARP) as standard surgery. The aim of this research was to determine continence in patients with anorectal malformation after PSARP action. Methods: This study was a descriptive analytical categorical research with cross sectional design. The data were obtained from patients’ medical records and questionnaire given to patients underwent PSARP in Wahidin Sudirohusodo Hospital and network hospitals from June 1 to December 1, 2018. The analysis was done to 60 children ranging from 5 to 8 years old. Most of them were male (56.7%) ranging from 5 to 6 years old (53.3%). Results: The results of the research indicated that based on malformation subtype, most of them suffered from rectourethra fistula (40.0%) with continence problem (61.7%). There was no significant correlation between sex and continence problem (p >0.05). However, it was seen that the percentage of continence subjects was higher in female (65.4%) than in male (58.8%), while the percentage of soiling and constipated subjects was higher in male than in female. Rectourethra fistula was found more frequently in male than in female (70.6%), while vestibuler fistula was found more frequently in female (69.2%). There was no significant correlation between age and defecation problem (p >0.05). However, the percentage of continence and soiling subjects was higher in 5-6 years children then the one for 7-8 year children, while the percentage of constipated subjects was higher in 7-8 year children (21.4%) than 5-8 year children (18.8%). Conclusions: Gender differences in the outcome of children with anorectal malformations must be considered. Men with perineal fistula were likely to experience continence and constipation than women with perineal fistulas. Women with perineal fistulas and vestibular fistulas had almost similar outcome.